Screening Pola Makan pada Pasien Diabetes Mellitus dengan Food Frequency Questioner - Nur Isnaini; Isna Hikmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine dietary screening in patients with diabetes mellitus with a food frequency questioner. This research method is a descriptive study by looking at the type of food staples, vegetables, fruits and other foods and beverages using the food frequency questionnaire. The range of consumption is in the range of daily, weekly, monthly or yearly. The results of the study, the most frequently consumed foods by DM patients in Puskesmas 1 Cilongok are as many as 24 people (60%) and followed by tempe consumption as many as 22 people (55%) with a frequency of eating> 1x / day. Vegetables that are often consumed are kale as many as 34 people (85%) and fruits that are often consumed are as many as 35 mango (87.5%) and bananas as many as 21 people (22.5%). Conclusion, Screening of DM patients is not only by type of food but it is also necessary to measure the amount and hours of meals so that they can see the type of amount and time because food is one of the causes of DM. Keywords: Diabetus Melitus, Food Frequency Questioner